Sustainable luxury: integrating circular design principles into the high fashion segment - Kornieva, Tetiana (Global Prosperity, 2025)
Abstract. The relevance of the study is determined by the growing need to integrate the principles of sustainable development into the high fashion industry in the context of increasing environmental challenges and the transformation of the value orientations of luxury brand consumers The purpose of the article is to provide a scientific justification for the possibility of combining the principles of the circular economy with the aesthetic, symbolic, and brand value of luxury fashion without losing its exclusivity. The research methodology is based on a combination of systemic and structural-functional approaches, conceptual analysis of the theory of circular economy, comparative analysis of the mass and luxury segments of the fashion industry, as well as qualitative analysis of empirical cases of leading luxury brands. The study found that circularity in the high fashion segment is implemented according to a design-oriented logic that differs from industrial models of mass production. It was found that upcycling of premium fabrics in luxury fashion functions not as a tool for waste disposal, but as a form of creating new aesthetic and symbolic value. It has been proven that limited production cycles and manual labor create conditions for the integration of circular solutions at the design stage. It has been substantiated that eco-ethical practices, under conditions of selective integration, can strengthen brand exclusivity rather than undermine it. A conceptual model of the balance between eco-ethics and exclusivity is proposed, verified through empirical cases of luxury brands. The practical significance of the results lies in the possibility of using the proposed approaches by designers, creative directors, and managers of luxury brands to develop sustainable development strategies that combine environmental responsibility with the preservation of the cultural and aesthetic uniqueness of high fashion.